Fibronectin regulates anoikis resistance via cell aggregate formation. (28th June 2021) - Han, Hyeong-jun; Sung, Jee Young; Kim, Su-Hyeon; Yun, Un-Jung; Kim, Hyeryeong; Jang, Eun-Ju; Yoo, Ha-Eun; Hong, Eun Kyung; Goh, Sung-Ho; Moon, Aree; Lee, Jae-Seon; Ye, Sang-Ku; et al.
Abstract: The loss of cell-matrix interactions induces apoptosis, known as anoikis. For successful distant metastasis, circulating tumor cells (CTCs) that have lost matrix attachment need to acquire anoikis resistance in order to survive. Cell aggregate formation confers anoikis resistance, and CTC clusters are more highly metastatic compared to single cells; however, the molecular mechanisms underlying this aggregation are not well understood. In this study, we demonstrated that cell detachment increased cell aggregation and upregulated fibronectin (FN) levels in lung and breast cancer cells, but not in their normal counterparts. FN knockdown decreased cell aggregation and increased anoikis. In addition, cell detachment induced cell-cell adhesion proteins, including E-cadherin, desmoglein-2, desmocollin-2/3, and plakoglobin. Interestingly, FN knockdown decreased the levels of desmoglein-2, desmocollin-2/3, and plakoglobin, but not E-cadherin, suggesting the involvement of desmosomal junction in cell aggregation. Accordingly, knockdown of desmoglein-2, desmocollin-2, or plakoglobin reduced cell aggregation and increased cell sensitivity to anoikis. Previously, we reported that NADPH oxidase 4 (Nox4) upregulation is important for anoikis resistance. Nox4 inhibition by siRNA or apocynin decreased cell aggregation and increased anoikis with the downregulation of FN, and, consequently, decreased desmoglein-2, desmocollin-2/3, or plakoglobin. The coexpression of Nox4 and FN was found to be significant in lung and breast cancer patients, based on cBioPortal data. In vivo mouse lung metastasis model showed that FN knockdown suppressed lung metastasis and thus enhanced survival. FN staining of micro tissue array revealed that FN expression was positive for human lung cancer (61%) and breast cancer (58%) patients. Furthermore, the expression levels of FN, desmoglein-2, desmocollin-2, and plakoglobin were significantly correlated with the poor survival of lung and breast cancer patients, as per the Kaplan-Meier plotter analysis. Altogether, our data suggest that FN upregulation and enhanced desmosomal interactions are critical for cell aggregation and anoikis resistance upon cell detachment. Highlights: Cell aggregation is critical for anoikis resistance. Cell detachment upregulates FN. FN enhances cell aggregation and anoikis resistance.